The Association between Solo versus Group Obstetrical Practice Model and Delivery Outcomes - Bardos, Jonah; Loudon, Holly; Rekawek, Patricia; Friedman, Frederick; Brodman, Michael; Fox, Nathan S. (American Journal of Perinatology, 2019)
Objective To determine if women under the care of obstetricians in solo practice have different delivery outcomes from women in a group practice.Study Design This is a retrospective cohort of live, term, singleton, vertex (LTSV) deliveries at one hospital from 2011 to 2015. We compared outcomes between women whose obstetrician was in solo practice with women in a group practice model.Results There were 18,214 LTSV deliveries by private obstetricians. Solo obstetricians were more likely to deliver at night (41.0 vs. 37.5%, p = 0.002) and less likely to induce labor (22.6 vs. 30.6%, p < 0.001). Solo obstetricians had a significantly higher rate of cesarean delivery (35.7 vs. 27.2%, adjusted odds ratio, aOR: 1.53, 95% confidence interval, CI [1.32, 1.78]), but also had a significantly lower rate of shoulder dystocia (0.4 vs. 1.4, aOR: 0.42, 95% CI [0.19, 0.89]), third or fourth degree lacerations (1.6 vs. 2.4%, aOR: 0.56, 95% CI [0.35, 0.914]), and neonatal intensive care unit admission rates (3.2 vs. 6.2%, aOR: 0.57, 95% CI [0.42, 0.77]).Conclusion In a large, tertiary care hospital, solo obstetricians have similar neonatal outcomes as group obstetricians. Their higher cesarean delivery rate is balanced by fewer shoulder dystocias and third/fourth degree lacerations, indicating a more conservative approach to labor management. Patient outcomes should not be a reason to discourage a solo practice model.
Keywords: Outcomes; solo; group; obstetrician